UMP vehicle booking using mobile application - Nurul Fazreen, Othman (2019)
In this era of globalization, advances in technology have escalated in line with the modernization of the country. The mobile technology created has gained a lot of attention because it has helped the community in terms of communication, time management, facilitating and solving all personal affairs and so forth. At Universiti Malaysia Pahang (UMP), the use of mobile applications is very limited because UMP still uses many manual forms in their administration and management activities. One of the activities that used the manual forms is vehicle booking. However, due to the manual process, overbooking cases usually happen, thus, may increase the approval times. Therefore, this project developed a mobile application for UMP Vehicle Booking using QR code technology to facilitate and help UMP students in managing vehicle booking by enhancing the use of manual forms to the mobile application. By using this application, students are able to make a booking for vehicle such as van or bus. Once the booking application is approved, one QR code will be generated and send to the students. Only those with the QR code will be able to see the vehicle details for the reservation.